Wireless mesh network data communications and reliability analysis for application deployment in anti-theft solutions - Van Rensburg, Roger (My University, 2020)
This research is an initiative from the High-Throughput Electronics Laboratory at the Uni- versity of the Witwatersrand to develop low-power wireless mesh networks for reliable data communications in the design of innovative anti-theft solutions. A network test-bench was developed, where millions of packets were transmitted and logged between interconnected nodes to analyse the quality of the network's service in a harsh indoor building environment. Similar methodologies as found in 'big data' analysis in particle physics were adopted to analyse the network's performance and reliability. The quality of service between multiple asynchronous transmitting nodes was determined and compared with the wireless technol- ogy routing protocol to assess coverage in large geographical areas. The statistical analysis conducted for each route and distributions revealed one, two and three-hop packet trans- missions have approximately 10, 20 and 30 ms round-trip times, respectively. Multimodal distributions in round-trip times of routes were present, consisting of an overlay of multiple normal distributions that indicate the presence of dynamic routing. The higher percentage of round-trip times for routes that fall outside three standard deviations from the mean of the distributions indicated reliability issues and was found more susceptible to packet loss. Overall, the wireless technology provided a total packet delivery ratio of 98.2% and found compatible with an IEEE 802.15.4 based low-power mesh networking protocol for low- throughput wireless communications. The deployment of anti-theft solutions is feasible in indoor or outdoor environments and the network can be used for various instrumentation applications in the control and monitoring of intelligent embedded systems.
A dissertation submitted in partial fullment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, 2020